Optimation of Temperature and Duration of Cocoa Beans Roasting in a CylindricalRoaster - Misnwai Jati; Sukrisno Widyotomo; Awad Sewed; Sugiyono . (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2005)
A small scale cylindrical type cocoa roaster has been designed to improve Indonesian mallholder income and commence utilization of cocoa-base products. Capacity of the roaster was at 15 kg dried cocoa beans. Operating condition of the instrument in terms of temperature and duration of roasting for cocoa powder production has been optimized by using Response Surface Methodology in the range of 110–140 C for the former and 20–60 minute for the latter. Variable of the study were temperature profile, peroxide value of cocoa butter, color and sensory properties of the resultant cocoa powder and microbial con tamination. Result of the study showed that cocoa bean’s temperature at the first 2–8 minute roasting was 30–50 C, before increased as high 10 C per minute to the adjusted temperature. Temperature and duration of roasting influenced interactively on peroxide value of cocoa butter, color and sensory properties of the resultant cocoa powder. An optimum roasting for cocoa powder preparation was obtained at temperature of 140 C and roasting time of 20 minute. Roasting treatment significantly reduced number of microbe in total plate count, however most probable number (MPN) of coliform in term of Escherichia coli was not detected. Key words : Cocoa bean, cocoa powder, cocoa butter, roasting, small scale cylindrical roaster, sensory properties, Escherichia coli.